2009
DOI: 10.1159/000189193
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Ovalbumin and CpG Motifs into Microparticles Protected Sensitized Mice from Anaphylaxis

Abstract: Background: Two major drawbacks of current subcutaneous specific immunotherapy are the risk to induce severe anaphylactic reactions and the need of multiple injections of the allergen to reduce IgE-mediated hypersensitivity. The sustained release of allergens over time provided by poly(lactide-co-glycolide) microparticles (MP) could mimic the current therapeutic schedule and decrease their allergenicity. Moreover, MP could also co-deliver Th1 immunoadjuvants, such as CpG motifs. Methods: Ovalbumin (OVA)-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…Further, linking CpG with allergen has reduced anaphylactic reactions to allergen when used either as a preventative therapy or as treatment in the form of s.c. injection or e.c. immunotherapy (114)(115)(116)(117)(118) in murine models. In humans, a similar TLR9 agonist, phosphorothioate oligodeoxyribonucleotide DNA, was coupled to ragweed antigen and showed some efficacy in a pilot s.c. injection study (119).…”
Section: Novel Therapeutic Strategies In Preclinical or Early Clinicamentioning
confidence: 99%
“…Further, linking CpG with allergen has reduced anaphylactic reactions to allergen when used either as a preventative therapy or as treatment in the form of s.c. injection or e.c. immunotherapy (114)(115)(116)(117)(118) in murine models. In humans, a similar TLR9 agonist, phosphorothioate oligodeoxyribonucleotide DNA, was coupled to ragweed antigen and showed some efficacy in a pilot s.c. injection study (119).…”
Section: Novel Therapeutic Strategies In Preclinical or Early Clinicamentioning
confidence: 99%
“…In case of aquasomes, antigens are presented partly by the B cell through the MHC II pathway leading to a good antibody response, while part of the antigen is cleaved within the antigen presenting cells and presented through MHC class I pathway, leading to a Th1/CTL response [13,14,16,18]. As it is well known, immunotherapy in humans should be based on the decrease of a Th2 response by enhancing the Th1 response, and this balance is achieved by increasing the activity of the Treg lymphocytes [7]. Treg cytokines (IL-10, TNF-α) play a key role in preventing IgE and Th2 expansion [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efficacy of SIT, there are concerns with the treatment including difficulties in standardization of allergen extracts, patient compliance due to frequent injections, long treatment duration and safety issues comprising local side-effects and risk of anaphylaxis [1,7]. One of the strategies to improve vaccines for SIT is to use adjuvants that can modulate the allergen-specific T cell response.…”
Section: Introductionmentioning
confidence: 99%
“…These NP formulations induced innate immune responses mediated by a TLR-2 and TLR-4 dependent manner and maduration of DC with a significant up-regulation of CD40, CD80, and CD86 and a biased Th1 present response in animal models [73,74]. This is an important finding since it has been recently shown that the use of multiple TLR-agonists carried by nanoparticles influence the induction of long-term memory cells, being the ultimate goal for any vaccine the stimulation of long-lasting protective immunological memory [75][76][77][78].…”
Section: Oralmentioning
confidence: 98%